Impact of BASILICA on the thrombogenicity potential of valve-in-valve implantations. (30th March 2021) - Plitman Mayo, Romina; Yaakobovich, Halit; Finkelstein, Ariel; Shadden, Shawn C.; Marom, Gil
Abstract: Subclinical leaflet thrombosis is becoming a major concern in valve-in-valve procedures, whereby a transcatheter aortic valve device is deployed inside a failed bioprosthetic surgical valve. Blood flow stagnation and prolonged residence times in the neo-sinuses have been suggested as possible explanations for leaflet thrombosis. The BASILICA technique, which was originally developed to treat coronary flow obstruction, has also been proposed as an alternative to reduce the risk of thrombus formation. The aim of this study is to understand the impact of BASILICA on the valve-in-valve thrombogenicity using computational fluid dynamics simulations. To this end, two Eulerian and two Lagrangian approaches were employed to estimate near-wall stagnation measures in eight valve-in-valve models. The models included an intact or lacerated Sorin Mitroflow surgical valve, and either a SAPIEN or Evolut transcatheter aortic valve device. The Lagrangian approaches predicted a high number of particles and vortices concentration in the proximal areas of the neo-sinuses, while the Eulerian approaches did so in the distal areas. As a consequence, this study demonstrated that Lagrangian approaches are better predictors of subclinical leaflet thrombosis, since they match experimental and clinical findings. Additionally, the SAPIEN valve possess a higher risk for developing leaflet thrombosis, and two lacerations are shown to provide the best results in terms of development of vortices and accumulation of particles within the neo-sinuses. This study highlights the potential of computational modeling in aiding clinicians in their decision-making in valve-in-valve and BASILICA procedures.